Turismo e patrimônio imaterial na pandemia: o caso do centro histórico de Belém (CHB) do Pará na Amazônia brasileira - Maria Augusta Freitas Costa Canal; Milene de Cássia Santos de Castro; Jorge Alex de Almeida Souza; Maria Goretti da Costa Tavares (Confins)
The present study aimed to analyze the patrimonialization in the historic center of Belém, of 04 intangible assets, Chiquita party, Pre-carnival, Carimbó and Arraial do Pavulagem. In addition to understanding how it was experienced, regarding public policies and impacts, during the pandemic period (2020-2021). The method used consists of qualitative research, direct observation, and monitoring of the social networks of the heritage assets examined by the study. Finally, the results showed that one of the strategies adopted for the dissemination of culture was the practice of lives